Characteristics of the Mixed Crude Jatropha Oil-Clove Oil - Gamayel, Adhes (Jurnal Teknik Mesin (JTM), 2016)
Crude jatropha oil (CJO) composed by triglycerides that consist of fatty acid and glycerol. CJO has high viscosity and low evaporation rate that cause ignition delay and imperfect combustion. Blending with lower viscosity and more volatile fuel can reduce it. In this study, CJO blend with clove oil (CO) in percentage of 5%, 10%, 15% and 20%.  The physical properties:  viscosity, heating value, and flash point were measured with international standard method (ASTM). The result indicates that more percentage of clove oil causes viscosity and flash point reduce while heating value increase. There is because molecular interaction between eugenol and triglyceride makes oscillation of molecule more active than before.